Inkjet‐Printed Xerogel Scaffolds Enabled Room‐Temperature Fabrication of High‐Quality Metal Electrodes for Flexible Electronics. (9th June 2022) - Wang, Shuaichen; Gao, Yuan; Huang, Qiyao; Guo, Xuyun; Yang, Anneng; Zhang, Yaokang; Zhuang, Qiuna; Chen, Dongdong; Chen, Lina; Ju, Xin; Hu, Hong; Zhang, Shengdong; et al.
Abstract: Inkjet‐printed metal electrodes with desirable morphologies and electrical properties are indispensable cornerstones for printable and flexible electronics. However, methods to fabricate metal electrodes nowadays mostly request the sintering of printed metal particles, which not only will easily damage heat‐sensitive plastic substrates, but also is difficult to achieve a smooth, neat, and highly adhesive electrode structure. Herein, a room‐temperature, solution‐processable copper (Cu) electrode is demonstrated to overcome the above issues. The key is to inkjet print a stable xerogel scaffold with high porosity, good uniformity, and smoothness for growing high‐quality Cu via electroless deposition. Xerogel‐based Cu electrodes exhibit a bi‐layer architecture, consisting of an upper thin‐film Cu (with an electrical conductivity of ≈1.2 × 10 7 S m −1 ) and a bottom Cu‐polymer interpenetrated network. The electrodes show an excellent uniformity, surface smoothness, high interfacial energy to the plastic substrates (690–970 mJ m −2 ), and good flexibility. Taking these merits, the electrodes can be patterned onto various plastic substrates and fabricate all‐solution‐processed electronic devices such as organic thin‐film transistors and organic electrochemical transistors with stable electrical performance. Abstract : A room‐temperature, solution‐processable method for growing high‐quality metals is demonstrated using inkjet‐printed xerogel as scaffolds. Xerogel‐based metal electrodes consist of an upper thin‐film metal and a bottom metal‐polymer interpenetrated network. The electrodes show an excellent uniformity and surface smoothness, high interfacial energy to the plastic substrates, and good flexibility, which are promising for fabricating various stable electronic devices.